Magnitude and Factors Associated with Precervical Cancer among Screened Women in Southern Ethiopia - Terefu Teka; Mesfin Kote; Gemechu Kejela; Tagel Getachew (Advances in Public Health)
Background. Cervical cancer is one of the major noncommunicable public health problems among the female population affecting not only the women but also the whole community. Annually, more than half a million new patients are diagnosed with it and over 270,000 deaths occur worldwide. There are very few research efforts conducted on prevalence and associated factors of specific target group in the region. So, this study tries to show the magnitude on all women screened for precervical cancer and serves as a secondary data for other research. Objective. The aim of the study was to assess magnitude of precervical cancer and associated factors among screened women in Arba Minch town and zuria woreda health institutions, southern Ethiopia. Methods. A facility based cross-sectional study was conducted in three health facilities at Arba Minch town and zuria woreda, southern Ethiopia, from June 2015 to June 2017. Data were collected by two nurses that are working in the area of expertise and one health officer as supervisor. Data of 528 screened clients were entered into Epi data version 3.1 using checklist, double data entry verification done and exported to SPSS version 20.0. After cleaning the data, descriptive analysis was done and multivariable logistic regression model was employed to identify predictors of precervical cancer. Finally, statistical significance was declared at P < 0.05. Result. In this study, the magnitude of precervical cancer is 27.7% [95%CI] (24.1-31.4)]. Having primary educational status (AOR [95% CI]) = 0.2 [0.1, 0.96)] and secondary educational status (AOR[95% CI]) = 0.1 [0.02,0.3]), having history of smoking [AOR (95% CI) = 3.7 (1.4-9.9)], having two and more than two life time sexual partners [AOR (95% CI) = 2.2 (1.1-4.7)], having age at first sexual intercourse less than eighteen years [AOR (95% CI) = 6.6 (3.14-13.0)] were significantly associated with precervical cancer. Conclusion and Recommendation. The magnitude of precervical cancer is 27.7% as shown in the result of the present study. Level of education, age at first sexual intercourse, history of smoking, and number of sexual partners were predictors of precervical cancer in this study. Thus, any cervical cancer prevention and control effort at the study area should address those predictors pointed out in the present study and should encourage to screen for precervical cancer.